2008
DOI: 10.1016/j.aquaculture.2008.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Depuration of microcystin-LR from the red swamp crayfish Procambarus clarkii with assessment of its food quality

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited.In most cases authors are permitted to post their version of the article (e.g. in Word or Tex form) to their pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 44 publications
2
19
1
Order By: Relevance
“…As a result, in these studies, a large amount of MC-LR in the diet was released with the faeces, decreasing the MC-LR content in organisms. In our study, pure toxin was used, and the results suggested that the tolerance of aquatic organisms to MC-LR might be much lower than what has been reported previously (Vasconcelos et al, 2001;Tricarico, 2008). In fact, MC-LR has diverse effects on species and animal sensitivity highly changed with the organism, the variant, and the mode of exposure (Hansson, 2007).…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…As a result, in these studies, a large amount of MC-LR in the diet was released with the faeces, decreasing the MC-LR content in organisms. In our study, pure toxin was used, and the results suggested that the tolerance of aquatic organisms to MC-LR might be much lower than what has been reported previously (Vasconcelos et al, 2001;Tricarico, 2008). In fact, MC-LR has diverse effects on species and animal sensitivity highly changed with the organism, the variant, and the mode of exposure (Hansson, 2007).…”
Section: Discussioncontrasting
confidence: 66%
“…Previous studies showed that, in natural lakes, P. clarkii accumulated more toxin in the intestine and less in the abdominal muscle (Tricarico, 2008). Other studies showed that, with regard to the oral route, cyanobacteria have higher toxic effects when fish were fed with crushed cells (released toxins) than when the fish were exposed to non-crushed cells (Jos et al, 2005).…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, P. clarkii is one of the most important vector of crayfish 'plague', carrying the pathogen (Aphanomyces astaci Schikora) as a chronic infection [18] and may also be an intermediate host for helminth parasites which can be transmitted to humans. Finally, P. clarkii is able to accumulate cyanobacterial toxins [19] and subsequently transfer them to their predators as well as to humans. Populations of P. clarkii are widespread in Europe, particularly in Spain, Italy and southern France, which have similar climatic conditions to Greece.…”
Section: Discussionmentioning
confidence: 99%
“…(Elder in the village of Vohiparara, Ranomafana National Park, Madagascar; after Jones, 2004) The most obvious use of crayfish is human consumption. As shown by Tricarico et al (2008), the abdominal muscle of P. clarkii has good nutritional qualities that are kept nearly constant during at least 21 days of stabulation at an ad libitum or restricted feeding regime. Crayfish muscles are characterized by high levels of proteins (reaching 13.24% on dry matter) and low levels of lipids (less than 0.8% on dry matter).…”
Section: Consumptionmentioning
confidence: 99%